The role of government in anti-social redistributive activities - Konstantinos Angelopoulos; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2005)
It is known that anti-social redistributive activities (rent seeking, tax evasion, corruption, violation of property rights, delay of socially beneficial reforms, etc) hurt the macroeconomy. But it is less known what is the role of government size as a determinant of such activities. We use data from 64 counties (both developed and developing) in 5-year periods over 1980- 2000. As a measure of anti-social activities, we use the ICRG index; as a measure of government size, we use the government share in GDP; and as a measure of government efficiency, we construct an index by following the methodology of Afonso, Schuknecht and Tanzi (2003). Our regressions show that what really matters to social incentives is the relation between size and efficiency. Specifically, while a larger size of government is bad for incentives when one ignores efficiency, the results change drastically when government efficiency is also taken into account. Only when our measure of size exceeds our measure of efficiency, larger public sectors are bad for incentives. By contrast, when efficiency exceeds size, larger public sectors are not bad; actually, in the case where efficiency is measured by government performance in the policy areas of administration, stabilization and infrastructure, larger public sectors significantly improve incentives.
Keywords: D7; H11; H3; 330; government and behaviour of agents; collective decision-making; Staatliche Einflussnahme; Wirtschaftliche Effizienz; Ökonomischer Anreiz; Staatsquote; Rent Seeking; Schätzung; Welt